Cost-effectiveness of adding empagliflozin to the standard of care for patients with heart failure with reduced ejection fraction from the perspective of healthcare system in Malaysia - Ong, Siew Chin; Low, Joo Zheng; Linden, Stephan (Frontiers in Pharmacology, 2023)
Objective: To determine the cost-effectiveness of adding empagliflozin to the standard of care (SoC) versus SoC alone for the treatment of patients with heart failure (HF) with reduced ejection fraction (HFrEF) from the perspective of the Ministry of Health (MoH) Malaysia. Methods: A cohort-based transition states model with health states defined as Kansas City Cardiomyopathy Questionnaire-Clinical Summary Score (KCCQ-CSS) quartiles and death was used to determine the lifetime direct medical costs and quality-adjusted life-years (QALYs) for both treatment groups. The risks of all-cause death, cardiovascular death, health state utilities were estimated from the EMPEROR-Reduced trial. Incremental cost-effectiveness ratio (ICER) was assessed against cost-effectiveness threshold (CET) defined by the country's gross domestic product (GDP) per capita (RM 47,439 per QALY) to determine cost-effectiveness. Sensitivity analyses were conducted to assess key model parameters' uncertainty on the ICER. A scenario analysis was performed using health states defined by New York Heart Association (NYHA) classes. Results: Compared to SoC alone, empagliflozin + SoC for the treatment of HFrEF was more expensive (RM 25,333 vs RM 21,675) but gained more health utilities (3.64 vs 3.46), resulting in an ICER of RM 20,400 per QALY in the KCCQ-CSS model. A NYHA-based scenario analysis generated an ICER of RM 36,682 per QALY. A deterministic sensitivity analysis confirmed the robustness of the model in identifying the empagliflozin cost as the main driver of cost-effectiveness. The ICER was reduced to RM 6,621 when the government medication purchasing prices were used. A probabilistic sensitivity analysis with CET of 1xGDP per capita reached 72.9% probability for empagliflozin +SoC against SoC being cost-effective. Conclusion: Empagliflozin + SoC compared to SoC alone for the treatment of HFrEF patients was cost-effective from the perspective of MoH Malaysia.